Mise en oeuvre et évaluation d'une méthodologie fondée sur la réalité virtuelle pour l'analyse de la prise d'informations visuelles du gardien de but de handball - Vignais, N. (Université Rennes 2, 2009)
Visual perception is a basic element allowing us to interact with our environment. During sport activities, the visual information uptake enable an athlete to extract and select visual cues necessary to anticipate the opposing action. In the field of sports, visual information uptake analysis has been widely carried out but all the methodologies used involve functional and material limits. The purpose of this work is to evaluate and introduce an innovative methodology based on virtual reality for analyzing visual information uptake. This methodology is applied to the handball goalkeeper activity in a duel situation. Firstly, the results obtained with our methodology and with a video-based technique are compared in order to demonstrate the interest of virtual reality in the field of sport. Secondly, we focused our attention on the setting-up of our methodology. Specifically, we aimed to analyze the influence of the graphical level of detail of the throwing action on the goalkeeper's performance. At last, our methodology is used to analyze the visual information uptake of the handball goalkeeper. More precisely, the relative importance of visual cues from ball trajectory and throwing motion is estimated.